x^2-x^2=x^2-x^2 _factorize : (x+x)(x-x)=x(x-x) _samplify by (x-x): (x+x)=x _then : 2x=x _so 2=1 how does it come that?????
Follow Math Help Forum on Facebook and Google+
Originally Posted by lebanon x^2-x^2=x^2-x^2 _factorize : (x+x)(x-x)=x(x-x) _samplify by (x-x): (x+x)=x_then : 2x=x _so 2=1 how does it come that????? $\displaystyle \left( {\forall x} \right)\left[ {x = x} \right]\; \Rightarrow \;\left( {\forall x} \right)\left[ {x - x = 0} \right]$
Title should be renamed to "find the mistake." Here it is: divide by (x-x): (x+x)=x Division by zero is undefined.
View Tag Cloud